Preparation method of diamond / aluminum composite material for reducing thermal expansion coefficient by using negative expansion material
By introducing negative expansion materials into diamond/aluminum composite materials and carrying out specific preparation and annealing treatment, the problem of mismatch in the thermal expansion coefficient of the material is solved, the regulation of the thermal expansion coefficient and the improvement of the thermal stability of the material is achieved, and the electronic equipment is satisfied. The need for thermal management materials.
Patent Information
- Application Number
- CN202411683714.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Diamond/aluminum composite materials are mismatched in electronic equipment, which leads to thermal stress, affecting the reliability and performance stability of the equipment.
By introducing negative expansion materials such as ZrW2O8, manganese nitrogen compound or Cu2-xMxV2O7, the thermal expansion coefficient of diamond/aluminum composite materials is adjusted, combined with ball milling process and annealing treatment, residual stress in the composite material is removed and the thermal stability of the material is improved.
The thermal expansion coefficient of diamond/aluminum composites is controlled, which reduces the thermal expansion coefficient and makes it closer to semiconductor devices, meets the requirements of thermal expansion coefficient matching of electronic packaging thermal management materials, and improves the mechanical properties and thermal stability of the materials.
Smart Images

Figure CN119491137A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a diamond / aluminum composite material containing a negative expansion material. Background Art
[0002] With the advent of the 5G era, the computing speed and power of electronic devices such as high-performance computer chips and communication base station power amplifiers are constantly increasing, and the demand for heat dissipation is becoming increasingly severe. Taking high-end CPUs as an example, the heat flux density can reach hundreds of watts per square centimeter, and even exceed 1000W / cm in some extreme conditions. 2 If the heat cannot be dissipated in a timely and effective manner, the temperature of the equipment will rise, which will affect its performance and reliability, and may even cause failure.
[0003] Diamond is the substance with the highest thermal conductivity in nature. Diamond / aluminum composite materials made by mixing it with aluminum have become a strong competitor for new thermal management materials. Diamond and aluminum have poor wettability, and there is a problem of poor interface bonding between the two. Domestic and foreign researchers have improved the interface bonding between diamond and aluminum by optimizing the preparation process, surface treatment of diamond particles, and alloying of the matrix metal, thereby improving the thermal conductivity of diamond / aluminum composite materials. Among them, the surface treatment of diamond particles and the modification of matrix alloying are carried out by introducing carbide-forming elements into the reinforcement diamond or the matrix aluminum, and improving the interface bonding by forming corresponding carbides at the interface between diamond and aluminum. Diamond / aluminum composite materials have great application potential in the field of thermal management materials for electronic packaging.
[0004] Nevertheless, the control of thermal expansion coefficient is still lacking in the research of diamond / aluminum composites. The thermal expansion coefficient of diamond is 1×10 -6 / K, while the thermal expansion coefficient of aluminum is as high as 23×10 -6 / K. In diamond / aluminum composite materials, increasing the volume fraction of diamond can reduce the thermal expansion coefficient of the composite material. However, the volume fraction of diamond cannot be increased infinitely due to the influence of stacking density, making it difficult for diamond / aluminum composite materials to fully meet the diverse needs of different electronic devices for thermal matching. If there is a mismatch in thermal expansion coefficients between the diamond / aluminum composite material and the semiconductor chip, when the ambient temperature changes, thermal stress will be generated due to the different degrees of thermal expansion. This thermal stress may cause the expansion of microscopic defects inside the material, such as the generation and propagation of cracks, which will have a serious negative impact on the reliability of the equipment and reduce the service life and performance stability of the equipment. Summary of the invention
[0005] The present invention provides a method for preparing a diamond / aluminum composite material which reduces the thermal expansion coefficient by using a negative expansion material in order to reduce the thermal expansion coefficient of the diamond / aluminum composite material, realize thermal expansion coefficient regulation of the diamond / aluminum composite material, and improve the thermal expansion coefficient matching between the diamond / aluminum composite material and a semiconductor.
[0006] The method for preparing the diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient is carried out according to the following steps:
[0007] 1. Weigh the raw materials
[0008] Weigh diamond particles, negative expansion material and aluminum matrix block as raw materials;
[0009] The volume fraction of the aluminum matrix block in the raw material is 30-38%, the volume fraction of the diamond particles is 55-60%, and the negative expansion material is the balance;
[0010] The negative expansion material is ZrW2O8, manganese nitrogen compound or Cu 2-x M x V2O7;Cu 2-x M x In V2O7, M is Mn or Ba, 0<x<2;
[0011] The average particle size of the diamond particles is larger than that of the negative expansion material;
[0012] The aluminum matrix block is one of pure aluminum or aluminum alloy;
[0013] 2. Preform Preparation
[0014] The negative expansion material and diamond particles weighed in step 1 are mixed and ball-milled, and then the mixed particles obtained after ball milling are filled into a graphite mold to obtain a preform;
[0015] 3. Composite material preparation
[0016] The preform obtained in step 2 is placed in a vacuum infiltration furnace, and the aluminum matrix block weighed in step 1 is placed on the preform; the infiltration furnace is evacuated, and then the preform and the aluminum matrix are preheated under a protective atmosphere, and after preheating, the furnace body is heated to 680-750° C., and then air pressure infiltration is performed at 680-750° C. for 5-15 minutes, and finally cooling and demolding are performed to obtain a composite material;
[0017] 4. Annealing of composite materials
[0018] Annealing the composite material obtained in step 3 to remove residual stress in the composite material to obtain a diamond / aluminum composite material containing a negative expansion material;
[0019] The annealing process in step 4 is to heat the composite material to 100°C at a rate of 5-10°C / min and keep it warm for 0.5-1h, then heat it to 200-450°C at the same heating rate and keep it warm for 0.5-6h, and finally cool it to room temperature at a rate of less than 5°C / min.
[0020] The present invention has the following beneficial effects:
[0021] 1. Based on the diamond / aluminum composite material, the present invention introduces a small amount of material with a negative expansion coefficient as a reinforcement. Due to different ratios of manganese nitrogen compounds or Cu 2-x M x V2O7 or ZrW2O8 have different thermal expansion coefficient characteristics. The thermal expansion coefficient of the prepared diamond / aluminum composite material is adjustable and can meet the requirements of thermal expansion coefficient under different service conditions through component design.
[0022] 2. The particle size of the negative expansion phase introduced in the present invention is smaller than that of the diamond particles, so that the negative expansion phase can effectively fill the gaps between the diamond particles. The negative expansion phase is introduced without reducing the volume fraction of diamond in the composite material, thereby achieving the regulation of the thermal expansion coefficient of the composite material.
[0023] 3. The present invention adopts a method of reducing the cooling rate and implementing annealing treatment to remove the residual stress in the composite material; in addition, annealing treatment is conducive to the transformation of g-ZrW2O8 to a-ZrW2O8, and the use of ZrW2O8 as a negative expansion phase is conducive to further reducing the thermal expansion coefficient. The thermal expansion coefficient of the diamond / aluminum composite material prepared by the present invention is 6 to 7.5×10 -6 / K, the thermal expansion coefficient is closer to that of semiconductor devices such as Si and GaN, and better meets the requirements of electronic packaging thermal management materials for thermal expansion coefficient matching.
[0024] 4. The present invention combines a negative expansion coefficient material with an aluminum matrix with a high expansion coefficient, which can offset a portion of the thermal expansion of aluminum through the negative expansion effect when the temperature changes, thereby reducing the overall thermal expansion coefficient of the composite material.
[0025] 5. ZrW2O8, manganese nitrogen compounds or Cu introduced by the present invention 2-x M x V2O7 can improve the mechanical properties of the matrix. Among them, the uniform dispersion of ZrW2O8 particles in the matrix can enhance the rigidity of the matrix and hinder dislocation movement; Cu 2-x M x The metal ions in V2O7 may diffuse with Al to form a transition layer, which effectively alleviates the internal stress caused by the mismatch of thermal expansion coefficients and improves the thermal stability of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the thermal expansion curve of the diamond / aluminum composite material with ZrW2O8 negative expansion material added prepared in Example 1 before and after annealing. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0028] Specific implementation method 1: In this implementation method, the preparation method of the diamond / aluminum composite material using negative expansion material to reduce the thermal expansion coefficient is carried out according to the following steps:
[0029] 1. Weigh the raw materials
[0030] Weigh diamond particles, negative expansion material and aluminum matrix block as raw materials;
[0031] The volume fraction of the aluminum matrix block in the raw material is 30-38%, the volume fraction of the diamond particles is 55-60%, and the negative expansion material is the balance;
[0032] The negative expansion material is ZrW2O8, manganese nitrogen compound or Cu 2-x M x V2O7;Cu 2-x M x In V2O7, M is Mn or Ba, 0<x<2;
[0033] The average particle size of the diamond particles is larger than that of the negative expansion material;
[0034] The aluminum matrix block is one of pure aluminum or aluminum alloy;
[0035] 2. Preform Preparation
[0036] The negative expansion material and diamond particles weighed in step 1 are mixed and ball-milled, and then the mixed particles obtained after ball milling are filled into a graphite mold to obtain a preform;
[0037] 3. Composite material preparation
[0038] The preform obtained in step 2 is placed in a vacuum infiltration furnace, and the aluminum matrix block weighed in step 1 is placed on the preform; the infiltration furnace is evacuated, and then the preform and the aluminum matrix are preheated under a protective atmosphere, and after preheating, the furnace body is heated to 680-750° C., and then air pressure infiltration is performed at 680-750° C. for 5-15 minutes, and finally cooling and demolding are performed to obtain a composite material;
[0039] 4. Annealing of composite materials
[0040] Annealing the composite material obtained in step 3 to remove residual stress in the composite material to obtain a diamond / aluminum composite material containing a negative expansion material;
[0041] The annealing process in step 4 is to heat the composite material to 100°C at a rate of 5-10°C / min and keep it warm for 0.5-1h, then heat it to 200-450°C at the same heating rate and keep it warm for 0.5-6h, and finally cool it to room temperature at a rate of less than 5°C / min.
[0042] This embodiment has the following beneficial effects:
[0043] 1. In this embodiment, a small amount of material with a negative expansion coefficient is introduced as a reinforcement on the basis of the diamond / aluminum composite material. Due to different ratios of manganese nitrogen compounds or Cu 2-x M x V2O7 or ZrW2O8 have different thermal expansion coefficient characteristics. The thermal expansion coefficient of the prepared diamond / aluminum composite material is adjustable and can meet the requirements of thermal expansion coefficient under different service conditions through component design.
[0044] 2. The particle size of the negative expansion phase introduced in this embodiment is smaller than that of the diamond particles, so that the negative expansion phase can effectively fill the gaps between the diamond particles. The negative expansion phase is introduced without reducing the volume fraction of diamond in the composite material, thereby achieving the regulation of the thermal expansion coefficient of the composite material.
[0045] 3. This embodiment adopts a method of reducing the cooling rate and implementing annealing treatment to remove the residual stress in the composite material; in addition, annealing treatment is conducive to the transformation of g-ZrW2O8 to a-ZrW2O8, and the use of ZrW2O8 as a negative expansion phase is conducive to further reducing the thermal expansion coefficient. The thermal expansion coefficient of the diamond / aluminum composite material prepared in this embodiment is 6 to 7.5×10 -6 / K, the thermal expansion coefficient is closer to that of semiconductor devices such as Si and GaN, and better meets the requirements of electronic packaging thermal management materials for thermal expansion coefficient matching.
[0046] 4. This embodiment combines a negative expansion coefficient material with an aluminum matrix with a high expansion coefficient, which can offset a portion of the thermal expansion of aluminum through the negative expansion effect when the temperature changes, thereby reducing the overall thermal expansion coefficient of the composite material.
[0047] 5. ZrW2O8, manganese nitrogen compounds or Cu introduced in this embodiment 2-x M x V2O7 can improve the mechanical properties of the matrix. Among them, the uniform dispersion of ZrW2O8 particles in the matrix can enhance the rigidity of the matrix and hinder dislocation movement; Cu 2-x M xThe metal ions in V2O7 may diffuse with Al to form a transition layer, which effectively alleviates the internal stress caused by the mismatch of thermal expansion coefficients and improves the thermal stability of the composite material.
[0048] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the diamond particles in step 1 are artificial single crystal diamonds, and the average particle size of the diamond particles is 100 to 500 μm.
[0049] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the average particle size of the negative expansion material in step one is 30 to 250 μm.
[0050] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: in step 1, the surface of the diamond particles is uncoated diamond or diamond coated with a metal coating, the thickness of the metal coating is 50 to 300 nm, and the metal coating is Ti, Cr, Mo or W.
[0051] Specific implementation mode five: The difference between this implementation mode and any one of specific implementation modes one to four is that the aluminum alloy described in step one is one of Al-Si alloy, Al-Si-Cu alloy, Al-Cu-Mg alloy, Al-Zn-Cu alloy, Al-Zn-Mg-Cu alloy, Al-Si-Cu-Mg alloy, or a combination of several of them.
[0052] Specific implementation method six: This implementation method is different from any one of specific implementation methods one to five in that: the ball milling process in step two is: the ball-to-material ratio is (10-30):1, the rotation speed is 50-300rpm, and the time is 0.5-10h.
[0053] Specific implementation method 7: This implementation method is different from any one of specific implementation methods 1 to 6 in that: the preheating temperature in step 3 is 450-550° C., and the preheating time is 1-3 hours.
[0054] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: the protective atmosphere in step three is one of helium atmosphere, argon atmosphere, and nitrogen atmosphere.
[0055] Specific embodiment 9: This embodiment is different from any one of specific embodiments 1 to 8 in that the air pressure during the air pressure infiltration in step 3 is set to 5 to 30 MPa.
[0056] Specific implementation method ten: This implementation method is different from any one of specific implementation methods one to nine in that: the cooling rate in step three is less than 2°C / min.
[0057] Example 1
[0058] The method for preparing the diamond / aluminum composite material using negative expansion material to reduce the thermal expansion coefficient in this embodiment is carried out according to the following steps:
[0059] 1. Weigh the raw materials
[0060] Weigh diamond particles, negative expansion material and aluminum matrix block as raw materials;
[0061] The volume fraction of the aluminum matrix block in the raw material is 38%, the volume fraction of the diamond particles is 60%, and the negative expansion material is the balance;
[0062] The diamond particles are artificial single crystal diamonds, and the average particle size of the diamond particles is 355 μm;
[0063] The negative expansion material is ZrW2O8;
[0064] The average particle size of the negative expansion material is 50 μm;
[0065] The diamond particles have no diamond coating on their surfaces;
[0066] The aluminum matrix block is pure aluminum;
[0067] 2. Preform Preparation
[0068] The negative expansion material and diamond particles weighed in step 1 are mixed and ball-milled, and then the mixed particles obtained after ball milling are filled into a graphite mold to obtain a preform;
[0069] The ball milling process in step 2 is as follows: the ball-to-material ratio is 15:1, the rotation speed is 200 rpm, and the time is 4 h;
[0070] 3. Composite material preparation
[0071] The preform obtained in step 2 is placed in a vacuum infiltration furnace, and the aluminum matrix block weighed in step 1 is placed on the preform; the infiltration furnace is evacuated, and then the preform and the aluminum matrix are preheated under a protective atmosphere, and after preheating, the furnace body is heated to 700° C., and then air pressure infiltration is performed at 700° C. for 10 minutes, and finally cooling and demoulding are performed to obtain a composite material;
[0072] The preheating temperature is 500°C and the preheating time is 1h;
[0073] The protective atmosphere is a helium atmosphere;
[0074] The air pressure during the air pressure infiltration is set to 15MPa;
[0075] The cooling rate is 1.5°C / min;
[0076] 4. Annealing of composite materials
[0077] Annealing the composite material obtained in step 3 to remove residual stress in the composite material to obtain a diamond / aluminum composite material containing a negative expansion material;
[0078] The annealing process is to heat the composite material to 100°C at a rate of 10°C / min and keep it at that temperature for 0.5h, then heat it to 200°C at the same heating rate and keep it at that temperature for 0.5h, and finally cool it to room temperature at a rate of 4°C / min.
[0079] Figure 1 The thermal expansion curves of the diamond / aluminum composite material with ZrW2O8 negative expansion material added before and after annealing obtained in Example 1. In the temperature range of 50-150°C, the average thermal expansion coefficient of the original and annealed composite materials increases from 9.63×10 -6 / K is reduced to 6.01×10 -6 / K, the thermal expansion coefficient of the diamond / aluminum composite material decreased by 37.6% after annealing.
[0080] Example 2
[0081] The method for preparing the diamond / aluminum composite material using negative expansion material to reduce the thermal expansion coefficient in this embodiment is carried out according to the following steps:
[0082] 1. Weigh the raw materials
[0083] Weigh diamond particles, negative expansion material and aluminum matrix block as raw materials;
[0084] The volume fraction of the aluminum matrix block in the raw material is 35%, the volume fraction of the diamond particles is 60%, and the negative expansion material is the balance;
[0085] The diamond particles are artificial single crystal diamonds, and the average particle size of the diamond particles is 355 μm;
[0086] The negative expansion material is a manganese nitrogen compound Mn3Zn 0.5 Ge 0.5 N;
[0087] The average particle size of the negative expansion material is 30 μm;
[0088] The diamond particles have no diamond coating on their surfaces;
[0089] The aluminum matrix block is pure aluminum;
[0090] 2. Preform Preparation
[0091] The negative expansion material and diamond particles weighed in step 1 are mixed and ball-milled, and then the mixed particles obtained after ball milling are filled into a graphite mold to obtain a preform;
[0092] The ball milling process in step 2 is as follows: the ball-to-material ratio is (10-30):1, the rotation speed is 50-300 rpm, and the time is 0.5-10 h;
[0093] 3. Composite material preparation
[0094] The preform obtained in step 2 is placed in a vacuum infiltration furnace, and the aluminum matrix block weighed in step 1 is placed on the preform; the infiltration furnace is evacuated, and then the preform and the aluminum matrix are preheated under a protective atmosphere, and after preheating, the furnace body is heated to 720° C., and then air pressure infiltration is performed at 720° C. for 10 minutes, and finally cooled and demolded to obtain a composite material;
[0095] The preheating temperature is 500°C and the preheating time is 1h;
[0096] The protective atmosphere is a helium atmosphere;
[0097] The air pressure during the air pressure infiltration is set to 15MPa;
[0098] The cooling rate is 1°C / min;
[0099] 4. Annealing of composite materials
[0100] Annealing the composite material obtained in step 3 to remove residual stress in the composite material to obtain a diamond / aluminum composite material containing a negative expansion material;
[0101] The annealing process is to heat the composite material to 100°C at a rate of 10°C / min and keep it at that temperature for 0.5h, then heat it to 200°C at the same heating rate and keep it at that temperature for 0.5h, and finally cool it to room temperature at a rate of less than 5°C / min.
[0102] After testing, the average thermal expansion coefficients (50-150°C) of the diamond / aluminum composite material prepared in Example 2 before and after annealing are 9.56×10 -6 / K, 7.54×10 -6 / K, the thermal expansion coefficient of the composite material decreased by 21.1% after annealing.
Claims
1. A method for preparing a diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient, characterized in that: The preparation method of the diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient is carried out according to the following steps:
1. Weigh the raw materials Weigh diamond particles, negative expansion material and aluminum matrix block as raw materials; The volume fraction of the aluminum matrix block in the raw material is 30-38%, the volume fraction of the diamond particles is 55-60%, and the negative expansion material is the balance; The negative expansion material is ZrW2O8, manganese nitrogen compound or Cu 2-x M x V2O7;Cu 2-x M x In V2O7, M is Mn or Ba, 0<x<2; The average particle size of the diamond particles is larger than that of the negative expansion material; The aluminum matrix block is one of pure aluminum or aluminum alloy; 2. Preform Preparation The negative expansion material and diamond particles weighed in step 1 are mixed and ball-milled, and then the mixed particles obtained after ball milling are filled into a graphite mold to obtain a preform; 3. Composite material preparation The preform obtained in step 2 is placed in a vacuum infiltration furnace, and the aluminum matrix block weighed in step 1 is placed on the preform; the infiltration furnace is evacuated, and then the preform and the aluminum matrix are preheated under a protective atmosphere, and after preheating, the furnace body is heated to 680-750° C., and then air pressure infiltration is performed at 680-750° C. for 5-15 minutes, and finally cooling and demolding are performed to obtain a composite material; 4. Annealing of composite materials Annealing the composite material obtained in step 3 to remove residual stress in the composite material to obtain a diamond / aluminum composite material containing a negative expansion material; The annealing process in step 4 is to heat the composite material to 100°C at a rate of 5-10°C / min and keep it warm for 0.5-1h, then heat it to 200-450°C at the same heating rate and keep it warm for 0.5-6h, and finally cool it to room temperature at a rate of less than 5°C / min.
2. The method for preparing a diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient according to claim 1, characterized in that: The diamond particles in step 1 are artificial single crystal diamonds, and the average particle size of the diamond particles is 100 to 500 μm.
3. The method for preparing a diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient according to claim 1, characterized in that: The average particle size of the negative expansion material in step 1 is 30 to 250 μm.
4. The method for preparing a diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient according to claim 1, characterized in that: Step 1: The diamond particles have no coated diamond or are coated with a metal coating on the surface. The thickness of the metal coating is 50 to 300 nm and the metal coating is Ti, Cr, Mo or W.
5. The method for preparing a diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient according to claim 1, characterized in that: The aluminum alloy in step 1 is one of Al-Si alloy, Al-Si-Cu alloy, Al-Cu-Mg alloy, Al-Zn-Cu alloy, Al-Zn-Mg-Cu alloy, Al-Si-Cu-Mg alloy, or a combination of several thereof.
6. The method for preparing a diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient according to claim 1, characterized in that: The ball milling process in step 2 is as follows: the ball-to-material ratio is (10-30):1, the rotation speed is 50-300 rpm, and the time is 0.5-10 h.
7. The method for preparing a diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient according to claim 1, characterized in that: The preheating temperature in step 3 is 450-550° C., and the preheating time is 1-3 hours.
8. The method for preparing a diamond / aluminum composite material using a negative expansion material to reduce thermal expansion coefficient according to claim 1, characterized in that: The protective atmosphere in step 3 is one of helium atmosphere, argon atmosphere and nitrogen atmosphere.
9. The method for preparing a diamond / aluminum composite material using a negative expansion material to reduce the thermal expansion coefficient according to claim 8, characterized in that: During the air pressure infiltration in step 3, the air pressure is set to 5-30 MPa.
10. The method for preparing a diamond / aluminum composite material using a negative expansion material to reduce thermal expansion coefficient according to claim 1, characterized in that: The cooling rate in step 3 is less than 2°C / min.
Citation Information
Patent Citations
SiC / Al2(WO4)3 / Al composite material with adjustable thermal expansion
CN104694775A
Anti-perovskite manganese nitrogen compound / aluminum composite material and preparation method thereof,
CN109680187A
Method for regulating and controlling expansion coefficient of light compact near-zero expansion metal matrix composite material
CN111041323A
Preparation method of low-expansion zirconium / aluminum tungstate composite material
CN114231784A
Low / zero expansion metal-based composite material with synergistically optimized comprehensive physical properties and preparation method of low / zero expansion metal-based composite material
CN114908267A
Cited By
Diamond and negative expansion particle reinforced aluminum matrix composite and preparation method
CN119592858A
A diamond and negative expansion particle-reinforced aluminum matrix composite material and its preparation method
CN119592858B